ADAT ISTIADAT DALAM KELUARGA AMALGAMASI BATAK DAN MINANGKABAU DI KECAMATAN TAMPAN DAN PAYUNG SEKAKI KOTA PEKANBARU - Simanjuntak, Sumiati; Tantoro, Swis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The ideal marriage to form a family is a marriage based on high background equations. The higher the level of differences of husband and wife background, the more difficult it is for them to socialize and apply the basic value to the child, the difference fiber can also trigger the occurrence of conflict. Nevertheless, in reality, there are still marriages in different societies such as different citizens, different religions, and different ethnic groups. The case of amalgamation from previous studies, no one discusses the customs among ethnic groups, especially Batak and Minankabau. This research was conducted in Kecamatan Tampan and Kecamatan Payung Sekaki. Problem formulation from this research, that is; 1. How is the application of customs values in the Batak and Minangkabau Amalgamation families? 2. How is the influence of customs values in the family of Batak and Minangkabau Amalgamasi? The type of this research is descriptive qualitative research, research subjects who become informants in this study as many as ten people who are married couples from five families. Technique of research subject taking done by two way, that is purposive sampling and snow ball sampling. The application and influence of customs values in the Batak and Minangkabau amalgamation families is still done and has an influence in everyday life although there are some traditions that are no longer done, and its application has begun to experience the proess of adjusting to the customs and culture of the city, as well as the lack of understanding of the meaning of tradition . The existence of the dominant cultur of the Batak tribe, due to the strong values and customary rules of customary Batak which is binding. Keywords : Customs, Amalgamation, Batak, Minangkabau, Tampan District, Payung Sekaki District.